Pengembangan Model Pembelajaran Collaborative Artistic Platforms Terintegrasi dengan Projek Penguatan Profil Pelajar Pancasila Untuk Optimasi Mahasiswa PPG di Sekolah Mitra - Ike Ratnawati; Diana Tien Irafahmi; Habiddin; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to develop a Collaborative Artistic Platforms learning model that is integrated with the Pancasila Student Profile Strengthening Project, in order to optimize the abilities of PPG (Professional Teacher Education) students at partner schools. This model is designed to improve collaborative skills, creativity and understanding of Pancasila values through interactive artistic activities. Research methods include model development, implementation in the field, and evaluation of effectiveness through qualitative and quantitative approaches. The research results show that this learning model is effective in increasing student involvement, their understanding of Pancasila values, as well as more creative and collaborative teaching abilities. It is hoped that this model can become a reference in developing a PPG curriculum that is more innovative and relevant to educational needs in Indonesia.